The ecological footprint of dwelling construction in Spain. (May 2015) - González-Vallejo, Patricia; Marrero, Madelyn; Solís-Guzmán, Jaime
Graphical abstract: Highlights: Ninety-two dwelling construction projects in Spain are evaluated. The most important factor in the EF calculation is construction materials. Detached houses generate an EF that is 1.5 times higher than multi-family buildings. Abstract: The construction industry is well known for its high impact on the environment; an even higher impact has taken place in recent years due to the real-estate bubble which has resulted in a surplus in the construction of dwellings in many countries. In Spain, about 500, 000 dwellings were constructed during 2006–2010, which represent a 2% increase in four years. In the present work, a methodology is defined as the first step towards the creation of an effective assessment of the Ecological Footprint of this type of construction. The procedure is based on the project budget and its bill of quantities, organized by means of a systematic construction-work breakdown structure which divides the work into three major categories: materials, manpower, and machinery. Each stream generates partial footprints (i.e. energy, food, mobility, construction materials, and waste). Ninety-two dwelling construction projects, which represent the most commonly built dwellings in Spain per statistical data from the authorities, are evaluated and their ecological footprints are determined. The indicator is sensitive to various building typologies, which range from detached houses to multi-family buildings. Detached houses generate an ecological footprint per square metre constructed of 1.5 times higher than that of 4-floor multi-family buildings and the indicator remains practically constant for taller buildings. This emphasises that not only is the traditional Spanish construction of a compact city with multi-storey buildings environmentally better from the mobility standpoint, but also from the building construction standpoint.